2009
DOI: 10.1016/j.jcrs.2009.05.052
|View full text |Cite
|
Sign up to set email alerts
|

Determination of albumin sorption to intraocular lenses by radiolabeling and confocal laser scanning microscopy

Abstract: Silicone and PMMA IOL materials showed BSA sorption near the lens surface only, while BSA penetrated deep into the hydrophilic acrylic IOL matrix. Combining the qualitative CLSM method and quantitative radiolabeling technique provided detailed information on protein interactions with implantable biomaterials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 52 publications
(54 reference statements)
2
4
0
Order By: Relevance
“…The above findings are in accordance with a report that serum albumin sorption is limited to the surface region of hydrophobic IOLs but penetrates deep into hydrophilic acrylic IOLs [8]. Other researchers have also reported that although hydrophobic IOLs develop and bind adhesive molecules such as vitronectin and collagen type IV less than hydrophilic IOLs, hydrophobic IOLs showed much more fibronectin binding on their surface than hydrophilic IOLs [9].…”
Section: Discussionsupporting
confidence: 92%
“…The above findings are in accordance with a report that serum albumin sorption is limited to the surface region of hydrophobic IOLs but penetrates deep into hydrophilic acrylic IOLs [8]. Other researchers have also reported that although hydrophobic IOLs develop and bind adhesive molecules such as vitronectin and collagen type IV less than hydrophilic IOLs, hydrophobic IOLs showed much more fibronectin binding on their surface than hydrophilic IOLs [9].…”
Section: Discussionsupporting
confidence: 92%
“…However, due to the attachment of a probe, conformational changes can occur, that may expose interior lysines to the outside which may then allow more dye molecules to attach. In the case of BSA and LY, we determined in a previous study a change of ∼5% in size and charge for BSA, comparing conjugated with unconjugated BSA over the incubation time of up to 14 days 66. These findings, and the fact that the DOL was determined to be <3, confirmed that the BSA remained in an acceptable conformational state throughout the experiment when conjugated with LY.…”
Section: Discussionsupporting
confidence: 56%
“…In the case of BSA and LY, we determined in a previous study a change of $5% in size and charge for BSA, comparing conjugated with unconjugated BSA over the incubation time of up to 14 days. 66 These findings, and the fact that the DOL was determined to be <3, confirmed that the BSA remained in an acceptable conformational state throughout the experiment when conjugated with LY. The native structure of both human and bovine serum albumin has 35 cysteines, of which 34 are typically paired with disulfide bonds to cystines and the sulphydryl group of the single Cys-34 remains mainly unbound.…”
Section: Discussionmentioning
confidence: 63%
“…In the case of the RGD-adsorbed sample, the high fluorescence may have resulted from the sorption phenomenon (i.e. molecules penetrated into the inner space of the hydrophilic acrylic polymer) [87] . Although the extreme condition of autoclaving had been applied to remove the surface-adsorbed peptides, a large amount of FITC-RGD peptides was “sorbed” inside the polymer, which could explain the low cell coverage of the FITC-RGD-adsorbed surface.…”
Section: Discussionmentioning
confidence: 99%